Enhancing Culinary SMEs Revenue in Burneh District, Bangkalan Through Halal Certification Optimization - Karim, Moh.; Dzikrulloh, Dzikrulloh (El-Qist: Journal of Islamic Economics and Business (JIEB), 2025)
This research aims to explore the implementation, response, and economic impact of halal certification on culinary Small and Medium-sized Enterprises (SMEs) in Burneh District, Bangkalan Regency, Indonesia. Employing a quantitative, field-based research design with a causal approach, data were collected through surveys and interviews with 12 SME owners across various business categories. The findings reveal that while awareness of halal certification and government support is relatively high, significant challenges remain in the certification process—particularly due to the lack of certified halal slaughterhouses and the complexity of procedural requirements. Despite these efforts, halal certification has not yet led to a significant increase in SMEs’ revenue, as most consumers—particularly in Muslim-majority Madura—do not actively verify the halal status of products, assuming all local culinary offerings are inherently halal. This study contributes to the global discourse on halal assurance by emphasizing the cultural, regulatory, and practical barriers to certification uptake in local economies. It recommends future research to investigate consumer behavior toward halal labeling and to assess long-term income impacts in regions with mandatory halal certification enforcement. Moreover, international comparative studies may further illuminate how halal certification contributes to economic empowerment across diverse Muslim communities.